FAKTOR-FAKTOR YANG MEMENGARUHI KOMPETENSI PETANI DALAM MELAKUKAN USAHA TANI PADI DI KOTA SINGKAWANG - Abelia Diwani; Josua Parulian Hutajulu; Komariyati (Jurnal Pertanian Agros, 2026)
Farmer competence is an important factor in increasing rice farming productivity, both from a technical and managerial perspective. This study aims to analyze the factors that influence farmer competence in rice farming in Pajintan Village, East Singkawang District, Singkawang City. The variables studied include age, education level, farming experience, effectiveness of agricultural extension, and government support as independent variables, and farmer competence as the dependent variable. This study used a survey method with 76 rice farmers as respondents. The analysis technique used was multiple linear regression to determine the influence of each factor on farmer competence. Farmer competence was measured based on a combination of technical and managerial aspects through a closed-ended Likert-scale questionnaire. The results showed that factors that significantly influence farmer competence are age, education level, experience, agricultural extension, and government support. The most dominant factor influencing farmer competence is the effectiveness of agricultural extension